Quality of Life and Some Related Factors of Elderly People in Turkmen County, Iran - Shahnaz Moalemi; Maryam Eri; Amene Sadat Sheykholeslami; Arezoo Sadegh Ghelichi; Abbas Malvandi (Golestan University Of Medical Sciences, 2019)
Background and objectives: Aging and its consequences are one of the major demographic issues in the world. The aim of this study was to determine quality of life and some related factors in elderly people living in Turkmen County (Iran) in 2017. This cross-sectional, descriptive-analytic study was conducted on 300 elderly people aged 60 years and older who were living in the Turkmen County, Iran. The subjects were selected via stratified random sampling. Data were collected using the World Health Organization Quality of Life-BREF Questionnaire. Data analysis was performed in SPSS software (version 16) using independent t-test, one-way ANOVA and nonparametric tests, such as Mann-Whitney U test and Kruskal-Wallis test. P-values less than 0.05 were considered statistically significant. Results: Of 300 subjects, 152 cases (50.7%) were women and 148 (49.3%) were men. The mean total score of quality of life was 54.4 ± 12.7. The mean standardized score of quality of life differed significantly depending on marital status, income level and number of children (P<0.05). There was a significant relationship between the mean standardized score of quality of life in terms of physical health and occupation status, age, income level and number of children. In addition, the mean standardized score of quality of life in the social relationship domain differed significantly based on gender, marital status, income level and number of children. Moreover, the mean standardized score of quality of life in the environmental health domain differed significantly based on occupational status and income level (P<0.05). Conclusion: Considering the impact of various factors on quality of life of the elderly, it is crucial to take measures for promoting quality of life in elderly women, unemployed elderly, people aged 80 years or older and those with a low income level.